METHODOLOGY FOR THERAPEUTIC PHYSICAL ACTIVITY TO IMPROVE HEALTH CONDITIONS IN WOMEN IN THE CLIMACTERIC - Ramos, Iliana Teresa Cantero; Regalón, Ramón Antonio Ibarra; Morrera, Carlos Miguel Ramírez (International Journal of Research -GRANTHAALAYAH, 2026)
Introduction: a research was carried out related to a methodology of physical activity and Therapeutics to modify the health conditions of women in the climacteric, with the intention to reduce morbidity and mortality due to conditions that are triggered in this stage and improve their quality of life. Therefore, a methodology was developed for the therapeutic physical activity of women in the climacteric, which facilitated the reduction of diseases and I will improve their health conditions and quality of life. Objective: Apply a methodology of therapeutic physical activity to improve the health conditions of women in the climacteric, in the Melissa textile workshop of the Municipality of Colombia, Las Tunas in the period from January 2024 to July 2025. Method: An intervention study was carried out with a universe of 65 women and a sample of 25 women in the climacteric was selected, following inclusion and exclusion criteria. The participants were applied a therapeutic physical activity methodology of mild and moderate aerobic physical exercises of low and medium intensity, with a systematicity of 3 times a week in their workplace and a duration of 45 minutes, in addition to individualized exercises for home practices with a duration of 30 minutes. The effects on the improvement of their health conditions were evaluated through questionnaires and in comprehensive care medical consultations. Results: Women between 45 and 49 years of age predominated, who showed a significant improvement in their health conditions, with a significant reduction in climacteric symptoms, including hot flashes, night sweats, irritability, insomnia and anxiety, in addition to body weight taking into account body mass index, blood pressure and symptoms related to the osteomyoarticular system. An increase in comprehensive health well-being was observed. Conclusions: The application of the therapeutic physical activity methodology systematically in their work environment and in their home of women in the climacteric allowed a positive impact on biopsychosocial well-being, helping to transform the unfavorable health conditions associated with the climacteric, changes were achieved in the general health status, improving quality of life, with the prevention and compensation of chronic non-communicable diseases and other conditions related to mental health